Sistem Monitoring Energi Listrik Menggunakan Sensor Hlw8012 Dan Mikrokontroler - Aziz Yulianto Pratama; Iwan Setiawan; Danang Hendrawan; Wahyu Yanuar Rizky (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Electronic equipment created today is synonymous with the use of electricity as an energy source. This will lead to an increase in the use and demand for electric energy for the use of electrical equipment every day. In addition, the availability of electrical energy is currently limited. These conditions require to economize on the use of electricity. Savings can be made when someone knows how much energy is used every day. To overcome this problem, a measuring instrument was designed in the form of a Wattmeter which has a real-time measurement system that can monitor the use of electric power every day through this tool and measurement data can also be accessed via a smartphone. This wattmeter uses an all in one sensor, namely the Hlw 8012 energy meter to measure RMS current, RMS voltage, and VA RMS equipped with Clock and PWM. From the results of these data will be uploaded to a cloud and then monitored through the blink application which has been designed to display data in the form of numbers and graphics according to the results on the tool. The results of measurement and monitoring of the tool that has been made using the Hlw 8012 sensor by obtaining 2 sensor data values ​​(current and voltage) are obtained for very good voltage values ​​between 0 - 2%, while for current values ​​reaching 5-10%. Error error in the current value due to the pulse output from the HLW8012 IC, thus causing an error in the power value, as well as the tolerance value of the HLW8012 IC of ± 5%.